Systematic review on problem-based learning in Science teaching - Judimar Teixeira da Silva; Ivoneide Mendes da Silva (Universidade Federal do Oeste da Bahia, 2020)
Problem-based learning is a methodology that uses the real-life problem to direct the teaching and learning process. The objective of this article was to build a systematic review study to identify a brief state of the art of using the PBL method in the teaching and learning process in Science Education in basic education. Systematic review (SR) is an effective method of analysis as it allows new research trends to emerge in the academic field. For this, an SR of scientific articles was held in events and magazines in the area of education, and theses and dissertations in a digital library from 2008 to 2018, using the terms Problem based learning (PBL) and Problem based learning. 32 eligible academic productions were considered, submitted to full reading and content analysis. The results point to the potential of PBL in basic education, which can be applied in the construction of scientific concepts, however when it comes to teacher training, short courses at universities is still the predominant model.